Mechanism of liver regeneration: 20-year bibliometric analyses - Qi, Jingshu; Dai, Yunkai; Sun, Xin; Liu, Chenghai (Frontiers in Pharmacology, 2023)
Objectives: To explore the most influential countries, institutions, journals, authors, research hotspots, as well as trend of the mechanism of liver regeneration (LR) in recent 20 years by using bibliometric analysis. Methods: Literatures associated with the mechanism of LR were retrieved from the Web of Science Core Collection on 11 October 2022. CiteSpace [6.1.R6(64-bit)] and VOSviewer [1.6.18] were used to perform bibliometric analysis. Results: A total of 18956 authors from 2900 institutions in 71 countries/regions published 3563 studies in different academic journals. United States was the most influential country, and University of Pittsburgh was the most published institution. Xu Cunshuan had the most published articles, whereas Michalopoulos George K was the most frequently co-cited author. The journal HEPATOLOGY was both the most published publication and the most frequently co-cited one in this field. Furthermore, origin and subsets of hepatocytes during LR; new factors and pathways in the regulation of LR; cell therapy for LR; interactions between liver cells in LR; mechanism of the proliferation of residual hepatocyte and the transdifferentiation between cell; prognosis of LR were the hotspots related to the mechanism of LR. Besides, the emerging topic that we should pay attention to is the regeneration mechanism of severely injured liver. Conclusion: The bibliometric analysis provides a more comprehensive overview of the mechanisms of LR and provides important clues and ideas for scholars concerned with this field.